2014
DOI: 10.1371/journal.pone.0098886
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein-70 (Hsp-70) Suppresses Paraquat-Induced Neurodegeneration by Inhibiting JNK and Caspase-3 Activation in Drosophila Model of Parkinson's Disease

Abstract: Parkinson's disease (PD) is one of the most common neurodegenerative disorders with limited clinical interventions. A number of epidemiological as well as case-control studies have revealed an association between pesticide exposure, especially of paraquat (PQ) and occurrence of PD. Hsp70, a molecular chaperone by function, has been shown as one of the modulators of neurological disorders. However, paucity of information regarding the protective role of Hsp70 on PQ-induced PD like symptoms led us to hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 57 publications
3
56
0
Order By: Relevance
“…We also cannot exclude the possibility that other mitigating effects, such as the induction of heat shock (hs) proteins, obscured the effects of proteasome inhibition. Overexpression of hs proteins in adult flies provides neuroprotection against insults relevant to PD (Auluck et al, 2002, Shukla et al, 2014), and exposure to temperatures ≥ 34°C has been shown to significantly increase hs protein expression (Auluck et al, 2005). Temperatures ≤ 30°C do not significantly elevate hs proteins expression in the fly (Auluck et al, 2005) and the maximum temperature used in our experiments was 30°C.…”
Section: 0 Discussionmentioning
confidence: 99%
“…We also cannot exclude the possibility that other mitigating effects, such as the induction of heat shock (hs) proteins, obscured the effects of proteasome inhibition. Overexpression of hs proteins in adult flies provides neuroprotection against insults relevant to PD (Auluck et al, 2002, Shukla et al, 2014), and exposure to temperatures ≥ 34°C has been shown to significantly increase hs protein expression (Auluck et al, 2005). Temperatures ≤ 30°C do not significantly elevate hs proteins expression in the fly (Auluck et al, 2005) and the maximum temperature used in our experiments was 30°C.…”
Section: 0 Discussionmentioning
confidence: 99%
“…ER and cellular stress marker proteins such as BiP and Hsp70 have been shown to have elevated expression levels in response to toxic stress in various neurodegenerative disorders, and many reports have detailed the relationship between JNK and Hsp70 (28,29,(33)(34)(35). Mitochondrial protein SOD1 has been implicated in ALS, and its activity is critical against oxidative stress, a hallmark of various neurodegenerative diseases (36).…”
Section: Overexpression Of Sgk1 In Sh-sy5y Cells Regulates 6-ohda-indmentioning
confidence: 99%
“…The generation of ONOO − in the brain of PQ-exposed Drosophila was measured essentially following the protocol described recently [52] using dihydrorhodamine 123 (DHR 123; Cayman Chemical, MI, USA). Briefly, single-cell suspension of Drosophila brain was incubated with 20 μM DHR 123 dissolved in 0.01 M PBS (pH 7.4) for 10 min at 24±1°C followed by washing with 0.01 M PBS (pH 7.4) and pellet down by centrifugation (8,000−g for 10 min).…”
Section: Measurement Of Peroxynitrite (Onoo − ) Generationmentioning
confidence: 99%